The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fevo.2022.840105
|View full text |Cite
|
Sign up to set email alerts
|

High Exploration Behavior of Termite Propagules Can Enhance Invasiveness

Abstract: Social life is usually associated with enhanced propagule pressure, which increases the chance of introducing several individuals during a single introduction event. Social insects are therefore among the most successful invasive species, benefiting from rapid establishment and increased foundation success in new habitats. In termites, propagule pressure may also be increased by the development of reproductive individuals from a small group of foraging workers. This suggests that enhanced exploration activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Reticulitermes flavipes is a successful invasive species, introduced to many regions worldwide, such as France, Chile, and Uruguay (Clément et al 2001; Austin et al 2005; Su et al 2006; Eyer et al 2021), while A. parvulus has not been reported as introduced outside of its endemic range. The spatially expansive foraging range of A. parvulus is a potential characteristic enhancing invasiveness, as it increases the chance of being inadvertently picked up and transported abroad (Evans et al 2011, 2013; Pailler et al 2022); however, this species was mostly found tunneling in mulch areas but not inhabiting substantial pieces of wood. The absence of dense colony fragments within large pieces of wood may have restricted the opportunity for large fragments of colonies to be transported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reticulitermes flavipes is a successful invasive species, introduced to many regions worldwide, such as France, Chile, and Uruguay (Clément et al 2001; Austin et al 2005; Su et al 2006; Eyer et al 2021), while A. parvulus has not been reported as introduced outside of its endemic range. The spatially expansive foraging range of A. parvulus is a potential characteristic enhancing invasiveness, as it increases the chance of being inadvertently picked up and transported abroad (Evans et al 2011, 2013; Pailler et al 2022); however, this species was mostly found tunneling in mulch areas but not inhabiting substantial pieces of wood. The absence of dense colony fragments within large pieces of wood may have restricted the opportunity for large fragments of colonies to be transported.…”
Section: Discussionmentioning
confidence: 99%
“…Some lower termites nest and feed on a single piece of wood (one-piece nesters), while others (both in lower and higher termites) feed on several pieces of wood connected by networks of galleries (multiple-piece nesters), or build large nests separate from their food sources (separate-piece nesters; Abe 1987; Eggleton and Tayasu 2001). Variation in foraging patterns can also be found among species of the same genus (Mizumoto et al 2020; Janowiecki and Vargo 2022; Pailler et al 2022), and sometimes even among colonies within species (Mizumoto and Matsuura 2013). Different tunneling patterns have been reported in subterranean termites of the genus Coptotermes (Mizumoto et al 2020), where colonies of C. formosanus construct a small number of long tunnels, while C. gestroi colonies usually make a large number of short tunnels (Grace et al 2004, Lee et al 2007; Hapukotuwa and Grace 2014).…”
Section: Introductionmentioning
confidence: 99%